2020
DOI: 10.1590/1678-992x-2017-0224
|View full text |Cite
|
Sign up to set email alerts
|

Least limiting water range, S-index and compressibility of a Udalf under different management systems

Abstract: Agricultural areas in the region of Turuçu, on the Southeast Hillside in the state of Rio Grande do Sul (RS), Brazil present many examples of soil physical degradation. Accordingly, strategies aimed at evaluating and ameliorating the structural quality of soils should be developed to ensure the sustainable use of these areas. This study aimed to evaluate the least limiting water range (LLWR), S-index, compressibility parameters, organic carbon and the organic matter granulometric fractions of a Udalf under dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…C. L. R. de Lima, Dupont, et al. (2020) reported that the soil water contents at FC and corresponding to critical PR were the most limiting factors for a description of LLWR. Haghighi et al.…”
Section: Resultsmentioning
confidence: 99%
“…C. L. R. de Lima, Dupont, et al. (2020) reported that the soil water contents at FC and corresponding to critical PR were the most limiting factors for a description of LLWR. Haghighi et al.…”
Section: Resultsmentioning
confidence: 99%